Mediating Parenting Solutions In The Age Of Technology - Anna deDufour; Karlee M. Naylon; Karen A. Lash (Washington University Journal of Law and Policy, 2022)
During the COVID-19 pandemic, programs in all sectors underwent an unprecedented push toward virtual communication, enhanced accessibility, and the evolution of service delivery networks. In order to assess the role of virtual mediation alongside in-person and phone mediation options, a research team including the authors conducted a case study of M.A.R.C.H. Inc., a Missouri mediation program that helps parents resolve disputes around custody, access and visitation, and child support. The study utilized administrative data, client and mediator surveys, and interviews with mediators, parties, and parenting court stakeholders to compare measures of quality, accessibility, engagement, outcomes, and satisfaction across communication modes. The findings illustrate the benefits of providing parties and mediators with a range of options for communication to improve accessibility, outcomes, and levels of satisfaction. Continued program evaluation and evidence-informed practices will enable administrators and practitioners to maximize the benefits of online dispute resolution; identify and manage obstacles; and ensure the equitable, ethical application of technology in the family court system.
Keywords: Virtual Mediation; Accessibility; Missouri Mediation; Custody Disputes; Child Support; Communication Modes; Family Court System; Virtual Communications